DEVELOPMENT OF SPORT VOLUNTEERING AT UNIVERSITIES OF THE URAL FEDERAL DISTRICT - M. V. Pevnaya; D. F. Telepaeva (Высшее образование в России, 2018)
The article considers the topical problem of the role of sports volunteering in the development of the Russian students and the volunteer movement in the University environment. The authors present the main trends regarding the inclusion of volunteering in everyday practice and in the University management. Relying on a wide empirical base of sociological data in the Ural Federal district, the authors aim at concretizing features of personal development of students who have had an experience of participation in various activities as sports volunteers. This publication presents the results of mass survey of students (2017; N=1860, quota sampling). The presented data demonstrate the prevalence of sports volunteering among University students of the Ural macro-region. The researchers show the specificity of this activity and determine the degree of youth involvement in volunteerism, and development of certain personality characteristics of sports volunteers, and their willingness to constantly prove their competitiveness, adapt to permanently changing conditions and rules of life, change their personal educational path.